The duality of hope and challenges: a phenomenological study of first-year university students’ experiences in South Africa - Mason, Henry D. (Frontiers in Psychology, 2024)
In South Africa, access to higher education is a potential enabler of life chances. The transition from school to university is stressful, and while existing literature acknowledges students' difficulties, limited research has investigated hope during this period. Furthermore, recognising the limitations of individualistic approaches to previous studies on hope, this study emphasises the need for culturally sensitive research within a collectivist context. Interpretative Phenomenological Analysis was employed to gain an in-depth understanding of 22 first-year South African university students' lived experiences of hope and challenges during the critical transition from school to university. Data were collected using semi-structured interviews and analysed via an iterative process, incorporating strategies to ensure trustworthiness and credibility. Three themes emerged from the analysis: (1) students experienced affective and social duality when entering university, (2) hope was described as a multifaceted concept guiding students through periods of uncertainty, and (3) hope extended beyond academic aspirations and encompassed personal fulfilment and societal impact. The study reveals hope as a multifaceted concept shaping students' experiences and extending beyond academic aspirations to personal relevance and societal impact.Acknowledging the limitations of individualistic approaches to previous studies on hope, this study emphasises the need for culturally sensitive research within a collectivist context. Further, it is recommended that future research explore hope in diverse cultural contexts and that student support services be offered in light of cultural realities.